DUAL-FUNCTION COFFEE SKIN PEELING MACHINE TO IMPROVE THE WELFARE OF SUMBERCANDIK COFFEE FARMERS JELBUK JEMBER - Darsin, Mahros; Djumhariyanto, Dwi; Wibowo, Robertoes Koekoeh Koentjoro; Basuki, Hari Arbiantara; Danang Yudistiro, Danang Yudistiro; Lindriati, Triana (LPPM Univ. Ibn Khaldun Bogor, 2024)
Panduman Village, Jelbuk Jember District, is a fostered village by the University of Jember. Sumbercandik is one of the hamlets in Panduman Village with a geography of mountain slopes and hills and at an altitude that is very supportive for coffee farming/plantations. It is no wonder that the best coffee products are produced from this village. Ironically, the lives of many coffee farmers still fall into the pre-prosperous group. One of the reasons is that farmers sell coffee logs or wet-skinned coffee at relatively low prices. At the same time, factory-made chemical fertilizers have skyrocketed in price, and availability is strict. Various efforts have been made by the local government and other service teams related to these coffee farmers, but they have not touched those in Sumbercandik Hamlet. This community service seeks to uplift the economy of Panduman Village, especially the coffee farmers of Sumbercandik Hamlet, with the introduction of post-harvest coffee technology, utilization of coffee waste for fertilizer and briquettes, and management and cooperatives. This grant ceiling will carry out the proposal in three years. The first year was with the introduction of post-harvest technology in the form of wet and dry skin stripping (horn skin). In the second year, intensive drying techniques using technical and thermal methods. In addition, farmer group formation and simple production management. Year three, post-harvest waste processing technology. The first year's focus was on providing a coffee skin peeling machine. Each year will involve different lecturers with agricultural, management and cultural competencies. This activity is in line with the 2021-2025 RIPP of the University of Jember with the featured topic